PI3K/AKT/MTOR SIGNALING PATHWAY - A KEY PLAYER IN THE MOLECULAR LANDSCAPE OF MALIGNANT TRANSFORMATION OF ORAL LESIONS - Mihai Radu Moisa; Elena Claudia Coculescu; Marina Imre; Alexandra Ripszky; Bogdan-Ioan Coculescu; Silviu Mirel Pițuru (Romanian Society of Oral Rehabilitation, 2024)
Aberrant PI3K/AKT/mTOR/ pathway have been considered one of the starting points of various types of human cancer, including the oral squamous cell carcinoma (OSCC). The important role played by this signaling pathway in oncogenesis and cancer evolution, oriented the researchers' attention toward studies of AKT and the PI3K/AKT/mTOR axis in the context of malignant transformation of oral precancerous lesions. Consequently, this article's aim is an update of the possible key role played by the PI3K /AKT/mTOR axis on the oral lesions' malignant transformation stage. Oral potentially malignant disorders are defined as lesions that will most probably progress to malignant lesions of the oral cavity. These lesions are mainly represented by leukoplakia, erythroplakia, actinic cheilitis and lichen planus. PI3K/AKT/mTOR signaling cascade should be regarded as a crucial subject for additional research, focusing not only on the early identification of malignant transformations of oral lesions, but also on opening new therapeutic ways in order to prevent malignant transformation and OSCC evolution.